Learning and Pedagogical Field: some key Concepts - Rubio Gaviria, David Andrés; Mendoza Duarte, Rogger Stiphen (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The importance of this article lies on the fact that learning can be seen as a central concept in the pedagogical field on the basis of questions such as: what is the significance of “education and learning constitute nowadays a same practice of discourse”? Or even, what does it mean that “the contemporary teacher ensures the learning process”? The objective is therefore to propose some talking points that challenge the idea of learning as a merely pedagogical issue in order to rethink it as a topic that today becomes strategic for pedagogy. Moreover, in this article some analysis possibilities are shown to understand the role of the teacher at present, from at least three perspectives: the influence of developmental psychology and learning in education, the importance of a didactic method when learning disciplines at school and the Pedagogical Conceptual Field (PCF), a concept coined by the Pedagogical Practice in Colombia History Group.